Differences in vault jumps in women artistic gymnastics - Milicic, L.; Zivcic Markovic, K.; Kristicevic, T.; Grbovic, M.; Aleksic-Veljkovic, A. (International Scientific Congress Slovenian Gymnastics Federation, 2019)
The aim of this study was to determine the difference between vault jumps at old and new horse performed at the Olympic Games 2000. and Olympic Games 2016. in women artistic gymnastics. Research was conducted on a sample of 32 jumps. Sixteen jumps at apparatus (vault) finals competition were performed at the Olympic Games 2000. in Sydney, Australia. Other sixteen jumps were performed also in the vault finals, but at the Olympic Games 2016. in Rio, Brazil. Analyses of the vaults were done by video. Variables which are used was divided in two parts: type of the jumps (2, 3, 4, 5) and rotation (180°, 360°, 540°, 720°, 900°). Type of jumps was: 2=Handsprings, 3=Tsukahara, 4=Yurchenko, 5= Half-turn entry. Differences between the Olympic Games in type of jumps and rotations were calculated by T-test for independent samples and Mann-Whitney U Test for independent sample. Results of Mann-Whitney U Test have shown that at the level of statistical significance of p<,05 that there were differences between the Olympic Games in variable rotation. It seems that today´s vault is performed with much more rotation around longitudinal (LA) axis of the body, and around transversal it seems that they are the same despite the new vault table.